Bloomsbury Scientists Science and Art in the Wake of Darwin - Boulter, Michael (UCL Press, 2017)
Bloomsbury Scientists is the story of the network of scientists and artists living in a square mile of London before and after the First World War. This inspired group of men and women viewed creativity and freedom as the driving force behind nature, and each strove to understand this in their own inventive way. Their collective energy changed the social mood of the era and brought a new synthesis of knowledge to ideas in science and art. Class barriers were threatened as power shifted from the landed oligarchy to those with talent and the will to make a difference. A time of unexpected opportunities, from the new disciplines of Genetics and Ecology to Post-Impressionism and beyond, Michael Boulter seamlessly weaves together the stories originating from Bloomsbury's laboratories, libraries and studios. He narrates the breakthroughs of scientists such as Ray Lankester and Marie Stopes alongside the creative outputs of H. G. Wells and Virginia Woolf, among many others, and intricately connects them all through personal friendships, grievances, quarrels and affections. Bloomsbury Scientists offers a fresh and crucial perspective on this history at a time when the complex relationship between science and art continues to be debated.